Ecthyma gangrenosum mimicking cellulitis - Ishihara, Toru (Clin Case Rep, 2021)
This report has strong implications for carefully examining the common skin signs of cancer patients receiving chemotherapy. These signs can warn clinicians of the potential for severe infections such as fatal sepsis.